Developments of aneurysm rupture prediction method using fracture mechanics analysis - Alias, J.; Mohamad Mazwan, Mahat; Akramin, M. R.M. (2010)
This study attempted to investigate the aneurysms growth and rupture using numerical approach. The bulging and widening of the blood vessel is due to the weakening of its wall which may lead the patient to death if rupture point is reached. This phenomena occur due to blood dynamics parameters which driven under certain flow conditions. It also has a tendency to enlarge over the years, depending on several factors. In order to obtain the deformation profiles, the fluid structure interaction method (FSI) was utilized to obtain the wall conditions of aneurysm ruptured. In addition, the numerical modelling of aneurysms results the blood flow parameter of pressure and velocity inside aneurysm sac in the form of profile correlations. The FSI transferred these dynamics loads to exert the aneurysms wall to determine the respective deformations. It is expected to explain the effect of blood flow to the weakening vessel wall and rupture behaviour due to variable flow conditions. These results assist medical practitioner to the prediction of time and location of aneurysm ruptured.